1999
DOI: 10.21273/hortsci.34.5.839
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Strawberry Yield Response to Preplant Soil Fumigation with Combinations of Methyl Bromide–chloropicrin and Four Alternative Systems

Abstract: Yield for annual California strawberry (Fragaria ×ananassa Duch.) production systems in soils treated with combinations of methyl bromide–chloropicrin (MB:CP) were compared with four alternative soil treatment systems using meta-analysis. Studies represent 11 production seasons, and were conducted at three distinct locations in California. Fumigation with mixtures of methyl bromide (MB) and chloropicrin (CP) increased yield significantly compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…Reports published during the past 50 years have documented the benefits of preplant soil fumigation with a mixture of methyl bromide and chloropicrin for annual (Wilhelm et al, 1974;Wilhelm and Paulus, 1980) and perennial strawberry (Fragaria ×ananassa) production systems (Hancock et al, 2000). Recent research syntheses have shown that yield differences between plants cultivated in fumigated and nonfumigated soils increase over cycles of strawberry cultivation (Shaw and Larson, 1999). The increasing benefits of soil fumigation over time resulted from deterioration of soil environments with repeated cropping of strawberry in the absence of fumigation, rather than from accrued benefits of repeat fumigation.…”
Section: Methodsmentioning
confidence: 99%
“…Reports published during the past 50 years have documented the benefits of preplant soil fumigation with a mixture of methyl bromide and chloropicrin for annual (Wilhelm et al, 1974;Wilhelm and Paulus, 1980) and perennial strawberry (Fragaria ×ananassa) production systems (Hancock et al, 2000). Recent research syntheses have shown that yield differences between plants cultivated in fumigated and nonfumigated soils increase over cycles of strawberry cultivation (Shaw and Larson, 1999). The increasing benefits of soil fumigation over time resulted from deterioration of soil environments with repeated cropping of strawberry in the absence of fumigation, rather than from accrued benefits of repeat fumigation.…”
Section: Methodsmentioning
confidence: 99%
“…It was also in the late 1990s that the first meta-analysis on a plant pathology topic, the effect of preplant fumigation with methyl bromide (MeBr) versus chemical MeBr alternatives on the yield of strawberry in California, appeared in the literature (117). Interestingly, this topic was revisited in one of the most recently published plant pathology meta-analyses in late 2013 (14); a comparison of these two research syntheses thus can shed light on scientific advances in this active and important area of research over more than a decade.…”
Section: Meta-analysis In Plant Disease Epidemiology and Managementmentioning
confidence: 99%
“…The selection process yielded a total of 45 studies (entries) in the 1999 paper and 136 entries (of which 68 were from strawberry in California) in the 2013 paper. The results of the 1999 analysis (117) showed that MeBr + chloropicrin significantly and consistently increased yield compared with chloropicrin alone (by 9.6%), 1,3-dichloropropene + chloropicrin (14.4%), metam sodium (29.8%), and the nonfumigated check (94.4%), leading to the conclusion that there was no technically viable alternative for standard MeBr preplant fumigation in strawberry production in California. In contrast, the 2013 analysis (14) showed that several of these same alternative treatments were statistically equivalent to MeBr, most notably a 1,3-dichloropropene + chloropicrin 65:35 mixture at standard rate.…”
Section: Meta-analysis In Plant Disease Epidemiology and Managementmentioning
confidence: 99%
“…For the analysis of variance Tables (4-7), a widely accepted statistical method ''metaanalysis'' (Cochrane and Cox, 1957) was used that combined replications from identical experiments grown in the same field in different years; the total number of replications of the experiment was 20 replications per treatment per cultivar. Examples of the use of this type of analysis combining identical plant experiments from different years or laboratories is available in several references (Morgan et al, 2003;Shaw and Larson, 1999). Starter fertilizer (6N-24P-24K) pretreated with Admire was applied at a rate of 560 kgÁha -1 .…”
Section: Plot Establishment Nutrient Sources and Applicationmentioning
confidence: 99%